Financial Leverage, International Orientation, And Firm Performance - Hanin Rialsa (Universitas Sebelas Maret, 2016)
This paper re-examines the effect of leverage on firm performance by looking at the moderating effect of international orientation. This study uses data ofmanufacturing 93 firms listed in the Indonesian Stock Exchange over the period of 2011 – 2014 resulting in 372 observations. Results show that financial leverage has negative and significant effect on firm performance. Second, international orientation does not significantly moderate the relationship between financial leverage and performance. The more internationally oriented the firms; it does not imply that the effect of leverage on performance should be stronger.